Assessment of the Diversity of Animals in the Forest Ecosystems of Pantabangan–Carranglan Watershed Forest Reserve, Nueva Ecija, Philippines - Paz-Alberto, Annie Melinda; Serrano, Shirly C.; Juganas, Daryl A. (Silliman Journal, 2022)
The diversity of animals in the forested area of Pantabangan–Carranglan Watershed Forest Reserve was assessed. The four major groups of animals such as birds, mammals, reptiles, and amphibians were observed, described, identified, and classified. Birds and volant mammals were observed through standard mist netting and either sight or sounds. On the other hand, nonvolant mammals were observed or caught by traps and searching along their possible habitat. Amphibians were caught by hand, and the reptiles were observed through sightings. A total of 53 animal species were observed in the area under 30 families, where Families Columbidae, Pteropodidae, Muridae, Colubridae, Ceratobatrachidae, and Dicroglossidae were the most represented families. Of the observed animals, 40 species were identified up to species level, and 13 species were identified through sightings and sounds. A bird species “Sawsaw-it” (Cinnyris jugularis) got the highest importance value index of 19.32% and biodiversity indicator value of 17.5%. It was also the most common and the most dominant animal species surveyed in the forest ecosystem. Pantabangan–Carranglan Watershed Forest Reserve exhibited low-to-very low diversity. Six species were listed as vulnerable and 3 species as near threatened. There were 40 native species recorded. Furthermore, there were no introduced species recorded in Pantabangan–Carranglan Watershed Forest Reserve. Human activities such as timber poaching, forest fires, soil erosion, kaingin farming, mining, and wildlife hunting posed small-to-moderate impacts on the area.